MENINGKATKAN KETERAMPILAN MENULIS TEKS BERITA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) PADA SISWA KELAS XII MULTIMEDIA DI SMK NEGERI 1 SAMARINDA TAHUN PELAJARAN 2017/2018 - Noor Aidawati (Kantor Bahasa Kalimantan Timur, 2018)
It is a classroom action research. It discusses about how to improve news text writing skills using project based learning model in class XII Multimedia students of SMK Negeri 1 Samarinda in the academic year of 2017/2018. The subjects of this research are students of class XII Multimedia since their average scores are below minimum mastery criteria (MMC) compared to other classes. The data collected here are texts of learning outcomes, observations of student and teacher activities, and portfolios. The data validity is divided into technique validity and source validity. Technique validity is in the form of observations, the score of student projects, documentations of result projects, and interviews. In order to triangulate the data, the researcher collects the information from observers, students, and informants of the student projects. It applies qualitative descriptive techniques. The indicators used here are individual scores (MMC 75) and the classical scores (80% of MMC). On the first cycle, 24 students or 61.5% do not reach MMC and only 15 students or 38.5% reach MMC, while on the second cycle, 39 students reach MMC 75.